Situation of Neuromarketing Consulting in Spain - Núñez-Cansado, Marian; López López, Aurora; Caldevilla Domínguez, David (Frontiers in Psychology, 2020)
The latest research in Spain indicates that the most advanced neuromarketing consulting companies in the sector are those that have been able to innovate in the development of their own technologies and methodologies. Despite their reduced volume of business compared to total investment in Marketing and market research in our country, there are signs that suggest these companies have great potential to improve this sector, which is still to be explored. For this reason, this research straddling the ethnographic method and the theoretical-descriptive method, aims to help us better understand the characteristic features of this sector by actively listening to the professional voices that lead it. Its epistemological value lies in its contribution to understanding the business culture related to the professional development of neuromarketing in our country today. The study shows that the main human resources strategy of neuromarketing consulting companies is based on the creation of multidisciplinary work teams. In addition, most of them develop data analysis software, which they can safeguard under various types of copy right, and on other occasions they manage to patent them, to later apply them to the objectives and purposes of their company. This would also explain the widespread use of certain procedures and resources by the vast majority of the consulting companies investigated. Thus, the trend in the market is the implementation of different synchronization software to the available technological and methodological resources. Others have even gone so far as to create a new technological support to incorporate methodologies already in use. Therefore, this gives them exclusivity in their services and the necessary competitive advantage over their competitors. Among other factors, these inferences about how this sector really works are very likely to be very useful in the academic field, which will constitute a further step in generating critical thinking and in expanding the frontiers of knowledge around this disciplin